Перспективи газоносності відкладів грушівської світи Закарпатського прогину (Україна) - Лозиняк, П.; Місюра, Я. (Геологія і геохімія горючих копалин, 2009)
Наведено дані літолого-стратиграфічного вивчення відкладів грушівської світи нижнього міоцену.верхнього олігоцену (егер), що базуються на аналізі фактичного матеріалу. За розбивками свердловин побудовано карту товщин відкладів світи, зроблено висновки щодо початкового етапу розвитку Закарпатського прогину, а також наведено локалізацію найперспективніших ділянок для пошуків вуглеводнів. Grushiv suite is a component of the lowest link of Neogene sedimentary column of the Precarpathian Foredeep. Dark-colored thickness named Grushiv suite contains mainly aleurolites and subordinated to them layers and interlayers of marlstones, sandstones and argillites. Age analogues of Grushiv suite are considered to be the rocks of Laziv and Dunkovytska suites. The lithology-stratigtaphic description of rocks of Grushiv suite of Lower Miocene–Upper Oligocene (Eger) has been given in the paper. It is based on fund materials, core description and the results of laboratory experiments of capacity-filtration characteristics of rocks. Sediments of Grushiv suite are opened by deep boreholes in the lowest central part of Solotvyno depression of Precarpathian Foredeep, in Solotvyno, Grushiv, Tereblya and Danyliv areas (15 boreholes). Also, the map of thickness of Grushiv suite sediments has been compiled according to borehole data, opened up by its crosssection. Sediments of Grushiv suite are bedding as narrow strap of 5–7 km wide, but in Solotvyno about 12 km and length is more than 100 km. This narrow furrow form structure with average Carpathian northwest trend is filled up with terrigenous carbonate marine sediments which has sometimes thickness more than 500 m. The conclusions have been done concerning the beginning stage of Precarpathian Foredeep and location of the most perspective areas for hydrocarbon searching.